Fundamental Of Enterpreneurship (ENT 300) : Identification of business oppurtunity / Brandon Beckham Siali … [et al.] - Siali, Brandon Beckham; Abang Hasyim, Dayang Hasmiera Azreen; Larry, Nazel Isaac; Hazali, Nur Iffahanis (2019)
A lot of opportunities have been done by government to encourage Malaysian or Bumiputera to set involve in business since business ventures in Malaysia are conquered by Non-Bumiputera who is very good in grabbing the chance by starting the business as they see a good profit in it. As much as we are delighted about business, four of us will take the opportunity to start the business in group together as addition in supporting Malaysia for producing more Bumiputera entrepreneurs.